2018
DOI: 10.1080/00332747.2018.1480251
|View full text |Cite
|
Sign up to set email alerts
|

Mediators in the Association Between Affective Temperaments and Suicide Risk Among Psychiatric Inpatients

Abstract: Hopelessness, depression, and mentalization are all factors that mediate the relation between affective temperaments and suicide risk. Identifying factors that mediate the effects of affective temperamental makeup on suicide risk should enhance screening and intervention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Their results indicated the existence of positive relationships between hopelessness and suicidal ideation, regardless of changes in the severity of depressive symptomatology. This is consistent with our findings and seems to suggest a dynamic of independence between levels of hopelessness and depressive symptomatology which a direct effect on suicidal ideation and behavior (Horwitz et al 2017). Erbuto et al (2018 point out that hopelessness plays a crucial role in mediating between affective temperaments and suicidal risk.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Their results indicated the existence of positive relationships between hopelessness and suicidal ideation, regardless of changes in the severity of depressive symptomatology. This is consistent with our findings and seems to suggest a dynamic of independence between levels of hopelessness and depressive symptomatology which a direct effect on suicidal ideation and behavior (Horwitz et al 2017). Erbuto et al (2018 point out that hopelessness plays a crucial role in mediating between affective temperaments and suicidal risk.…”
Section: Discussionsupporting
confidence: 93%
“…In their meta-analysis, Franklin et al (2017) found that the five main categories for suicidal ideation in terms of the weighted magnitude of risk are, first, the prior ideation of suicide, hopelessness, diagnosis of depression, history of abuse of any kind, and, finally, the diagnosis of anxiety. Erbuto et al (2018), propose that in addition to the previous constructs, attention should be paid to psychological pain, mentalization processes (ability to reflect and understand one's mood) and dissociative symptoms as possible mediators of the association between affective temperaments (cyclothymic, depressive, hyperthymic, irritable, and possibly anxious temperament subtypes) and suicidal risk.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the present findings suggest that: hyperthymic temperament may be, at least partially, a selfish and reckless trait; self‐transcendence may be altruistic and not reckless; and self‐directedness may be altruistic but reckless. On the other hand, Erbuto et al showed that psychiatrically hospitalized patients with negative temperaments (similar to affective dysregulated temperaments) reported higher suicide risk, psychological pain, hopelessness, and depression, and less mentalization than patients with no prevalent temperament or hyperthymic temperaments. Also, Pompili et al showed that major depressive disorder patients were more likely to have higher Anxious Temperament, higher Hopelessness, and lower Hyperthymic Temperament scores, while bipolar I disorder patients more often had cyclothymic and irritable temperaments than patients with other axis I diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also suggested that hopelessness is related to childhood maltreatment [39,40]. Moreover, hopelessness is associated with suicide risk among psychiatric patients [41], particularly in those patients who have experienced childhood abuse and neglect [42]. Gibb et al [43], inspired by the "hopelessness model" of suicide risk [44], hypothesized that childhood maltreatment might contribute to the development of a negative cognitive style that exacerbates hopelessness, which, in turn, triggers suicidal ideation and behaviors.…”
Section: Introductionmentioning
confidence: 99%